Endogenous Emission Caps Always Induce a Green Paradox - Reyer Gerlagh; Roweno J.R.K. Heijmans; Knut Einar Rosendahl (Center for Economic Studies and ifo Institute (CESifo), 2019)
For any emission trading system (ETS) with quantity-based endogenous supply of allowances, there exists a negative demand shock, e.g. induced by abatement policy, that increases aggregate supply and thus cumulative emissions. We prove this green paradox for a general model and then apply it to the details of EU ETS. In 2018, new rules for a Market Stability Reserve (MSR) were agreed on and implemented. We show that abatement policies announced in early periods but realized in the future, are inverted by the new rules and increase cumulative emissions. We provide quantitative evidence of our result for a model disciplined on the price rise in the EU ETS that followed the introduction of the MSR.
Keywords: D59; E61; H23; Q50; Q54; Q58; 330; emissions trading; green paradox; EU ETS; environmental policy; dynamic modeling